An industry update: what is the latest news in therapeutic delivery?. (July 2017) - Simpson, Iain
This Industry Update covers the period from 1 through 30 April 2017, and is based on information sourced from company press releases, scientific literature, patents and various news websites. Biogen expanded its portfolio of developmental drugs targeting neurological diseases by licensing a drug from Bristol-Myers Squibb which is currently under investigation for the treatment of progressive supranuclear palsy. Takeda announced a deal with NuBiyota focused on developing treatments for gastrointestinal disorders, based on the manipulation of microbes living in the gut. Novartis announced an expansion of its neuroscience collaboration with Amgen as well as licensing of a developmental compound to treat dry eye. EmulateBio announced a collaboration with the US FDA to explore and evaluate its organs-on-chip technology in toxicological testing of food products, but which has wider opportunities in drug development. In the treatment of pulmonary hypertension, Vectura announced the commercial launch of its Fox nebulizer technology to deliver a Bayer drug and Respira announced a deal in which it exclusively licensed an inhaled drug-device product to United Therapeutics. Published research suggested that the benefit of pumps over multiple injections in the treatment of diabetes maybe more due to training than technology, and a group from the University of Pennsylvania showed that electrical stimulation of the brain can improve memory function but only when applied at the right time. Alzheon published work that explains the mechanism behind its developmental Alzheimer's drug.